KERENTANAN MASYARAKAT DALAM MENGHADAPI ANCAMAN GEMPA BUMI SESAR LEMBANG DI DESA LANGENSARI KECAMATAN LEMBANG KABUPATEN BANDUNG BARAT - Nur Sum Febrianti; Dede Kuswanda; Endah Dwi Winarni (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2021)
This study aims to determine the level of vulnerability in Sukamulya, Langensari Village, which is known as an earthquake-prone area because it is located in the Lembang fault area. Vulnerability is a condition of a community or society that leads to or causes an inability to deal with the threat of disaster. This research used a vulnerability measure which is divided into three aspects; physical, social, and economic vulnerability. This research used a quantitative approach with a descriptive method.Data collection techniques used are questionnaires, observation, and documentation reviews. The validity test of this research was the face validity and the reliability test with the Cronbach alpha reliability testin Langensari Village.